Heterogeneous pattern of gene expression driven by TTN mutation is involved in the construction of a prognosis model of lung squamous cell carcinoma - Liu, Zhao; Zhao, Xiaowen; Wang, Ruihong; Tang, Xiangyue; Zhao, Yuxiang; Zhong, Guanghui; Peng, Xin; Zhang, Chunlin (Frontiers in Oncology, 2023)
TTN is one of the mutated genes in lung cancer and plays a crucial role in the development of the disease. Thus, the specific mechanism through which it contributes to lung cancer has not been fully elucidated. We applied the Cancer Genome Atlas (TCGA) dataset to perform a TTN mutation analysis in lung squamous cell carcinoma (LUSC). We collected a LUSC dataset from the TCGA database, obtained patients’ clinical information, and applied bioinformatics statistical methods for mutation analysis and prognostic survival. We then validated the results with the Gene Expression Omnibus (GEO) dataset. Our study showed that the incidence of TTN mutations in LUSC was 73.00% and was correlated with the survival of patients with LUSC. The screening of the main prognostic factors SLC34A2, BARX1, and HOXC10 driven by TTN mutation heterogeneous expression by least absolute shrinkage and selection operator (LASSO) Cox analysis could provide valuable clues on the prognosis of TTN gene mutations in LUSC.